Importance of knowledge-attitude-practice to enhance university technology transfer - Sivaraos, Subramaniam; S.H., Yahaya; Pujari, Satish; M.S., Salleh; Kadirgama, Kumaran
Malaysia Innovative Year 2010 was launched by the 6th Prime Minister. Since then, numbers of innovation activities were in raise, but not the technology transfer. Thus, every public university in Malaysia were urged to establish Technology Transfer Office (TTO) to address this issue. Unfortunately, the numbers are still low despite having the capacity, capability, resources, and funding in place and strongly supported by the university management. Therefore, the non-technical attributes such as Knowledge, Attitude, and Practice (KAP) were considered for investigation to study if they could potentially be the reasons affecting technology transfer in the universities. Thus, researchers from selected public universities in Malaysia namely lecturers and postgraduates were chosen as the respondents. A specially designed questionnaire for this study has been designed to expose the technology transfer gap in universities. This study reveals all three investigated attributes namely Knowledge, Attitude, and Practice (KAP) scores were below 55% which are considered low as compared to other critical studies. It is also evident that, the KAP interaction effects are significant to which they cause the technology transfer in the universities not to prosper as expected.